THE EFFECT OF FINANCIAL LITERACY, INCOME, AND LIFESTYLE ON PERSONAL FINANCIAL MANAGEMENT AMONG YOUNG WORKERS IN DENPASAR CITY - Swari, Ni Made Ary Diana Pradnya; Gama, Agus Wahyudi Salasa; Astiti, Ni Putu Yeni (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
Financial planners should be able to manage their funds by setting aside a portion of their income for savings and investments. This study aims to determine the influence of financial literacy, income, and lifestyle on financial management. The research method used is quantitative. The population consists of young workers in Denpasar City, and the sample size is 100 people. Data analysis techniques include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Determination Coefficient, F-Test, and t-Test. The results of the study show that financial literacy has a positive and significant effect on financial management, income has a positive and significant effect on financial management, and lifestyle has a positive and significant effect on financial management. The researcher's suggestion is that young workers in Denpasar should always use their money wisely, set aside money that can be used to help their families, always manage their lifestyle well, and always be active and focused in taking courses that discuss financial management.